Antibacterial potential ethanol extract of beluntas leaves (Pluchea indica L) to Streptococcus sanguinis - Wilma ADIWIJAYA; Riani SETIADHI; Vinna Kurniawati SUGIAMAN (Journal of Syiah Kuala Dentistry Society, 2022)
Recurrent aphthous stomatitis (RAS) is one of the most common oral diseases in the community, with a prevalence of 5-66%, with one of the predisposing factors being Streptococcus sanguinis. Treatment for RAS has been symptomatic and supportive, including antiseptic mouthwash such as chlorhexidine gluconate 0.2% or topical corticosteroids (triamcinolone acetonide 0.1% in Orabase). However, these drugs have some side effects. Treating herbal ingredients such as Beluntas leaves low prices and minimal side effects. The active compounds in Beluntas leaves are phenols, tannins, flavonoids, saponins, triterpenoids, essential oils, terpenoids, and many compounds known to have antibacterial activity. Methods: This study aimed to determine the minimum inhibitory level (MIC), and minimum killing rate (MBC) of 96% ethanol extract of Beluntas leaves on the growth of Streptococcus sanguinis. MIC was measured by broth microdilution technique with DMSO solvent 10% and eight concentrations of beluntas extract. Chlorhexidine gluconate 0.2% was used as a positive control for the comparison compound. Furthermore, the MBC test was carried out using the total plate count method for treatments that gave the MIC value. One Way Anova analysis with Post Hoc Tukey was used to determine the significant difference between treatments. Results: The ethanol extract of Beluntas leaves (Pluchea indica L) has a Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) for the growth of Streptococcus sanguinis with a minimum inhibitory concentration of 3.95 g/mL and a minimum concentration of 7.8 g/mL. Conclusion: The ethanol extract of Beluntas leaves (Pluchea indica L) has the potential as an antibacterial against Streptococcus sanguinis. KEYWORDS: Recurrent aphthous stomatitis, Streptococcus sanguinis, ethanol extract of beluntas leaves, Minimum Inhibitory Concentration, Minimum Bactericidal Concentration